STAGES OF REGIONAL FOOD SECURITY PROVISION - Krasnoperova, E.A.; Donnik, I.M.; Yuldashbayev, Yu.A.; Leshcheva, M.G.; Kulakov, V.N.; Chylbak-ool, S.O. (Scientific Journal of Pedagogy and Economics, 2020)
The problem of national economic security, which includes guaranteed food provision in the regions, occupies one of the pivotal places in the politics of economically developed countries of the world. Issues of food security and agricultural development should be a priority; without them, all conversations about national security are meaningless. Over the past 20 years, a lot of funds and efforts have been invested in the development of agriculture in Russia, the results of these efforts say it all. Russia has become the largest exporter of food raw, completely covers the needs of the population in chicken eggs, poultry, and pork. Despite significant advances in food security, many problems need to be solved immediately. The problem of food security provision at the federal and regional levels should be approached comprehensively. First of all, it is necessary to comprehend and realize that economic life develops according to its very specific laws, the complex interaction of which, ultimately, determines the state of the economy. The current situation with the position of food security can be assessed as not quite satisfactory. The article outlines the problems of food security in the Chelyabinsk region and the relationship of its tasks, the growth of life expectancy, and the working capacity of the population. Four stages of their duration and features of tasks at each stage are substantiated. The term for the full achievement of food security is designed for 12 years, improving the nutritional structure and increasing its usefulness will increase life expectancy by 8-12 years, which is consistent with state policy in the economic and social spheres.